รูปแบบการพัฒนาสมรรถนะครูด้านการจัดการเรียนรู้เชิงรุก ด้วยชุมชนแห่งการเรียนรู้ทางวิชาชีพ โรงเรียนตะคร้อพิทยา อำเภอไพศาลี จังหวัดนครสวรรค์: A Model of Active Learning Competency Development for Teacher with Professional Learning Community: Takhro Pittaya School, Phaisali District, Nakhon Sawan Province - saisopa, sripawan (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
The objectives of this research were 1) to survey the teachers' need for the competency development in active learning management 2) to create and examine the quality of the model 3) to study the results of using the model and 4) to assess the teachers' satisfaction towards a model of active learning competency development for teacher with professional learning community. The instruments of this research were a questionnaire on current condition and expected condition, model assessment form, the tests and the assessments of active learning management, and an attitude and a satisfaction assessment. The data were analyzed by mean and standard deviation. The population was 25 teachers at Takhro Pittaya School. The results showed that 1) the results of the survey of the teachers' need for the competency development in active learning management on current condition was overall at moderate level, and the expected condition was at the highest level. 2) The results of the creating and examining the quality of the model of active learning competency development for teacher with professional learning community were consisted of five elements; principle, objective, content, development process, measurement and evaluation. 3) The results of using the model found that the teacher has had the knowledge and understanding about active learning management after training more than before training to statistically significant at level .05. Then the average scores of teachers' ability in active learning management were 3 cycles - the values were respectively 3.45/4.03 and 4.45. The teachers' attitude towards an active learning was overall at high level. 4) The results of the assessment of teachers' satisfaction towards the model of active learning competency development for teacher with professional learning community were overall at high level.